Strategi Guru Geografi dalam Menciptakan Kelas yg Kondusif di Kabupaten Kampar Timur - Airin Syafira; Fauziah Hafifah; Naj'la, Naj'la; Nia Silvina Daulay; M. Zawil; Sonia Julita; Ade Irma (CV. ITTC INDONESIA, 2025)
This study aims to analyze the strategies used by geography teachers in creating a conducive classroom environment in East Kampar District by examining aspects of teacher personality, learning methods, and classroom management. The research employs a literature review method by analyzing five scientific articles related to learning strategies, learning environments, and the role of teachers in fostering a comfortable classroom atmosphere. The analysis was conducted by extracting key findings from each article and linking them to the learning needs of geography education in the research area. The findings indicate that geography teachers can create a conducive classroom environment through effective communication, empathetic attitudes, and interactive learning strategies such as Discovery Learning, which enhance student activity and participation. In addition, the arrangement of the physical and social classroom environment, as well as teachers’ ability to address curriculum-related challenges, also influence the conduciveness of learning. Overall, appropriate strategies can improve students’ comfort, motivation, and engagement in geography learning.